Cadmium Pollution From Zinc‐Smelters up to Fourfold Higher Than Expected in Western Europe in the 1980s as Revealed by Alpine Ice. Issue 10 (23rd May 2020) - Legrand, M.; McConnell, J. R.; Lestel, L.; Preunkert, S.; Arienzo, M.; Chellman, N. J.; Stohl, A.; Eckhardt, S.
Abstract: Estimates of past emission inventories suggest that toxic heavy metal pollution in Europe was highest in the mid‐1970s for lead and in the mid‐1960s for cadmium, but these previous estimates have not been compared to observations. Here, alpine ice‐cores were used to document cadmium and lead pollution in western Europe between 1890 and 2000. The ice‐core trends show that while lead pollution largely from leaded gasoline reached a maximum in ~1975 as expected, cadmium pollution primarily from zinc smelters peaked in the early‐1980s rather than in ~1965 and was up to fourfold higher than estimated after 1975. Comparisons between ice‐core trends, estimated past emissions, and state‐of‐the‐art atmospheric aerosol transport and deposition modeling suggest that the estimated decreases in cadmium emissions after 1970 were based on overly optimistic emissions reductions from the introduction of pollution control devices and other technological improvements. Plain Language Summary: Cadmium and lead are among the most toxic heavy‐metal pollutants and identified by international conventions as priority contaminants for emissions reduction. Anthropogenic emissions in Europe previously estimated from commodity production statistics are uncertain; comparison with long‐term pollution records extracted from well‐dated ice cores provides a means of evaluating these estimates. Alpine ice‐core records spanning 1890 to 2000 show that lead pollution, mainly related to leaded gasoline use since the mid‐20th century, reached a maximum in the mid‐1970s as predicted by estimated past emissions. Surprisingly, however, cadmium levels primarily arising from zinc smelter emissions were up to fourfold higher than expected and decreased only after 1980, suggesting that previous reconstructions of past cadmium pollution had assumed overly optimistic emissions reductions from the introduction of pollution control devices and other technological improvements particularly after 1975. Contrary to previous emissions estimates, these new alpine ice‐core records show that western European pollution maxima for these two toxic metals coincided in the 1970s. This finding is important in terms of impact of Cd pollution on organisms that depends on concentration in the environment but also duration of exposure. Key Points: First evaluation of past cadmium and lead anthropogenic emissions in Europe by alpine ice records and model simulations over the Alps Maximum of cadmium pollution in Europe in 1980 instead of 1965 due to less efficient reduction of emissions than predicted Maximum pollution by cadmium from zinc smelters and by lead from leaded gasoline in the late 1970s in Europe